Prospects of E-Commerce Innovation in Increasing Students Consumer Trust - Wardihan Sabar (Universitas Negeri Surabaya, 2022)
Various innovations have been made to solve problems in increasing consumer confidence to shop safely on e-commerce portals. This study aims to determine the level of consumer confidence in the e-commerce innovation model, as well as to explore the academic point of view. The study used a descriptive approach. The number of respondents in this study was 61 respondents for Students consumers, and 3 explanations from the perspective of academics. The results of the study show various problems that are often experienced by consumers and make consumer confidence relatively low, including; the first is the issue of personal information security, and the second is the issue of conformity with consumer expectations. Consumers believe that buying and selling online increases their shopping effectiveness. In addition, consumers perceive that the presence of an e-commerce portal provides great benefits for the ease of finding goods and services that consumers need. The tendency of consumers to shop online in the future will continue to increase, but consumers have not fully demonstrated the belief that mainstream online buying and selling in the future is more desirable than shopping in shopping centers